7-foot man-eating chicken : an NBA agent's tall tales of finding clients under car, the 406-pound center, and the 700 million round-trip ticket to Athens /: an NBA agent's tall tales of finding clients under car, the 406-pound center, and the 700 million round-trip ticket to Athens. (2009) - Unknown
No abstract available